Enhancing Students Speaking Skills Through Project-Based Learning - Sintya Mutiara We (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
The mastery of English speaking skill is one problem for Indonesian learners so that it needs one particular treatment to overcome it. This study was aimed to investigate if Project-Based Learning (PjBL) was effective to improve speaking skills of the second year of non-English students in one private university in Semarang and how PjBL was able to influence their attitude to speaking. Quantitative and qualitative methods were used. Quasi-experimental research design was applied to 53 students. To collect data, instruments employed were speaking tests, observations, and interviews. The results showed that the experimental group had a better score compared to the control group. The previous mean score was 8.74, and the post mean score was 11.33. The range score of the experimental group and the control group was 3.70. Furthermore, Independent Sample T-test showed sig. value (2-tailed) of 0.00, which was lower than 0.05, indicating that there was statistically significant difference between the two groups. The results of the interviews also showed that the students gave positive attitudes towards the implementation of PjBL. Before the treatment the students had low motivation and confidence in speaking. After the 8 week-treatment, the finding showed that they felt enthusiastic and challenged during all the speaking projects. This method was successful to develop the students’ motivation and confidence to speak up in English.